2019
DOI: 10.1128/jvi.00382-19
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleoprotein and Phosphoprotein Are Major Determinants of the Virulence of Viral Hemorrhagic Septicemia Virus in Rainbow Trout

Abstract: Viral hemorrhagic septicemia virus (VHSV), a fish rhabdovirus, infects several marine and freshwater fish species. There are many strains of VHSV that affect different fish, but some strains of one genetic subgroup have gained high virulence in rainbow trout (Oncorhynchus mykiss). To define the genetic basis of high virulence in trout, we used reverse genetics to create chimeric VHSVs in which viral nucleoprotein (N), P (phosphoprotein), or M (matrix protein) genes, or the N and P genes, were exchanged between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 64 publications
6
35
1
Order By: Relevance
“…Interestingly, this amino acid change was identified also in our analysis, where aa signatures R and S were significantly associated with the high and low virulent phenotype, respectively. Similarly, a recent study using a chimeric VHSV generated by reverse genetics suggested that positions N46, N82, N83, and P39, also identified in our study, were putative markers of virulence ( Vakharia et al, 2019 ), highlighting once again the potential of the analytical model herein presented for predicting virulence determinants. Indeed, reverse genetics is the most appropriate tool to verify the SAPs identified in this work.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Interestingly, this amino acid change was identified also in our analysis, where aa signatures R and S were significantly associated with the high and low virulent phenotype, respectively. Similarly, a recent study using a chimeric VHSV generated by reverse genetics suggested that positions N46, N82, N83, and P39, also identified in our study, were putative markers of virulence ( Vakharia et al, 2019 ), highlighting once again the potential of the analytical model herein presented for predicting virulence determinants. Indeed, reverse genetics is the most appropriate tool to verify the SAPs identified in this work.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have attempted to link VHSV virulence to specific molecular markers based on phenotype information and/or genetic data ( Betts and Stone, 2000 ; Campbell et al, 2009 ; Dale et al, 2009 ; Einer-Jensen et al, 2014 ; Kim et al, 2014 ; Ito et al, 2016 , 2018 ; Baillon et al, 2017 ; Vakharia et al, 2019 ; Yusuff et al, 2019 ). However, because most of these attempts have been based on the visual inspection of a restricted number of sequences, the mechanisms underlying virulence are still elusive and lack statistical support.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations